Experimental validation of a three-port integrated topology to interface electric vehicles and renewables with the electrical grid - Monteiro, Vítor Duarte Fernandes (2018)
This paper presents the analysis and the experimental validation of an off-board three-port integrated topology (TPIT) used to interface electric vehicles (EVs) and renewables from solar photovoltaic (PV) panels with the electrical power grid. The TPIT is composed by three power converters sharing a single common dc-link, and it can operate in four different modes towards the future smart grids: (1) The EV batteries are charged with energy from the electrical power grid through the grid-to-vehicle (G2V) operation mode; (2) The EV batteries deliver part of the stored energy back to the power grid through the vehicle-to-grid (V2G) operation mode; (3) The energy produced by the PV panels is delivered to the electrical grid through the renewable-to-grid (R2G) operation mode; (4) The energy produced by the PV panels is used to charge the EV batteries through the renewable-to-vehicle (R2V) operation mode. In addition to individual action, the reorganization of these modes results in new combined operation modes. The paper presents the proposed power theory to control the TPIT, the current control strategies to manage the currents in ac and dc sides of the TPIT, and the details of the developed TPIT prototype, including the hardware and the digital control system. Experimental results that validate the TPIT operation modes are also presented.